From the Social Terminology of Chaghataid Ulus and Golden Horde: «Tabin» » - I.V. Zaytsev (Золотоордынское обозрение)
This note deals with the term Tabin occured in the Western Russian translation of the letter of the Golden Horde Khan Murtaza to the Polish king Kazimir (August 1484). The author believes that the word is Chaghataid تابين which means “the servant”. Tabin was a kind of military rank, the owner of which was close to a Khan, and served him as an adjutant or a page. We can assume the existence of such special elite military page corps at the court of Golden Horde khans, just as they existed in contemporary Timurid states.